Disruption of Long-Term Alcohol-Related Memory Reconsolidation: Role of β-Adrenoceptors and NMDA Receptors - Wouda, Jelte A.; Diergaarde, Leontien; Riga, Danai; Van Mourik, Yvar; Schoffelmeer, Anton N.; De Vries, Taco J. (Frontiers in Behavioral Neuroscience, 2010)
Disrupting reconsolidation of drug-related memories may be effective in reducing the incidence of relapse. In the current study we examine whether alcohol-related memories are prone to disruption by the β-adrenergic receptor antagonist propranolol (10 mg/kg) and the NMDA receptor antagonist MK801 (0.1 mg/kg) following their reactivation. In operant chambers, male Wistar rats were trained to self-administer a 12% alcohol solution. After 3 weeks of abstinence, the animals were placed in the self-administration cages and were re-exposed to the alcohol-associated cues for a 20-min retrieval period, immediately followed by a systemic injection of either propranolol, MK801 or saline. Rats were tested for cue-induced alcohol seeking on the following day. Retrieval session, injection and test were repeated on two further occasions at weekly intervals. Both propranolol and MK801 administration upon reactivation did not reduce alcohol seeking after the first reactivation test. However, a significant reduction of alcohol seeking was observed over three post-training tests in propranolol treated animals, and MK801 treated animals showed a strong tendency toward reduced alcohol seeking (p = 0.06). Our data indicate that reconsolidation of alcohol-related memories can be disrupted after a long post-training interval and that particularly β-adrenergic receptors may represent novel targets for pharmacotherapy of alcoholism, in combination with cue-exposure therapies.